Crustal Structure of the Northern Hikurangi Margin, New Zealand: Variable Accretion and Overthrusting Plate Strength Influenced by Rough Subduction. Issue 5 (19th May 2021) - Gase, Andrew C.; Van Avendonk, Harm J. A.; Bangs, Nathan L.; Bassett, Dan; Henrys, Stuart A.; Barker, Daniel H. N.; Kodaira, Shuichi; Jacobs, Katrina M.; Luckie, Thomas W.; Okaya, David A.; Fujie, Gou; Yamamoto, Yojiro; et al.
Abstract: Exploring the structure of convergent margins is key to understanding megathrust slip behavior and tsunami generation. We present new wide‐angle and marine multichannel seismic data that constrain the crustal structure and accretion dynamics of the northern Hikurangi margin. The top of the basement of the Hikurangi Plateau is overlain by a rough, 2–3 km thick layer of volcanic cover with P‐ wave velocities ( V P ) between 3 and 5 km/s. This volcanic cover contributes significantly to seismic reflectivity beneath the shallow subduction plate boundary. The frontal prism structure varies along‐strike from ∼25 km wide with imbricate thrust faults where accretion of trench sediments is undisrupted, to narrower (∼14 km) with slumps and branching, irregular thrust fault geometries, which may reflect lower sediment supply or past seamount collisions. A large thrust fault network in the inner prism with a seismically fast hanging wall indicates a mechanical boundary between a seismically faster deforming backstop and the seismically slower frontal prism. Near the coastline, V P increases between 2.8 and 4 km/s at 2–8 km depth and is 0.5–1.7 km/s slower than the southern Hikurangi margin. Low seismic wavespeeds and low vertical velocity gradients in the inner prism support the hypothesis that a weak overthrusting plate contributes to historic tsunami‐earthquakes and long duration seismic ground motion. Plain Language Summary: The northern Hikurangi margin is a subduction zone that generates hazardous earthquakes and tsunami, as well as months‐long slow slip events. Here, we use a controlled seismic energy source to image and map the seismic wavespeed of the overthrusting plate, downgoing plate—which is called the Hikurangi Plateau—and the megathrust fault that generates earthquakes. Thick layers of volcanic sediments and lavas on the Hikurangi Plateau produce bright reflections beneath the megathrust fault. Volcanic mountains on the subducting plate, called seamounts, are shown to influence the volume of sediment that scrapes off the downgoing plate and complicate the way that thrust faults form in the overthrusting plate. An increase in seismic velocity and change in fault geometry in the overthrusting plate indicates that the upper plate can be divided into a weak outer prism of young off‐scraped sediments and a stronger inner prism of older, deformed sediments. However, the strength of the interior of the overthrusting plate is still relatively weak. A weak overthrusting plate with slow seismic wavespeeds is believed to promote larger than predicted tsunami and excessive shaking during earthquakes. Key Points: Sharp along‐strike contrasts in frontal accretion indicate variable sediment supply and past subduction of topography We identify a deformed inner prism with elevated seismic velocity and an accreted frontal prism divided by a network of thrust faults Low P‐ wave velocities in the overthrusting plate near Gisborne may contribute to tsunamigenesis and enhanced ground motion duration